O raciocínio geográfico em perspectiva: a geografia na BNCC brasileira e na indicazioni nazionali italiana - Lúcio Antônio Leite Alvarenga Botelho (2022)
The field of research in Geography teaching has been consolidated in recent decades. There is, at the moment, focused concern and investment regarding the development of didacticpedagogical actions that favor the overcoming of conventional classes and so-called traditional methods. In this context, we identified researchers concerned with a certain modus operandi of Geography that aims at the development and understanding of cognitive processes linked to the spatial order of things and phenomena. Therefore, terms such as Geographical Reasoning, as well as other similar concepts, are now objects of research. At the same time, there is a movement in several countries to adapt their teaching systems and regulations that govern basic education, where it is possible to perceive such trends. Based on this premise, the present thesis aimed to carry out an analysis of the curricular regulations that govern the stages of Ensino Fundamental, in Brazil, and of the Primo Ciclo di Istruzione, in Italy, using the comparative method and the Grounded Theory in the investigation of the assumptions of geographic education in the Base Nacional Comum Curricular (BNCC) and in the Italian regulations – Indicazioni Nazionali per il curricolo del Primo Ciclo –, despite the commitment to the development of Geographical Reasoning. To this end, we are anchor on the proposal by Roque Ascenção and Valadão (2014, 2016, 2017a, 2017b) and Roque Ascenção, Valadão e Silva (2018), which is based on the development of Geographical Reasoning through the mobilization of founding concepts of geographic science and its methodological tripod, based on the analysis of a geographic situation. In order to achieve the objectives of this research, what is investigated here was based on a work agenda that involved: (i) the identification of issues in the epistemology of geographic science and the development of Geography as a school subject, which led us to considerations about the importance of developing Geographical Reasoning; (ii) the presentation of proposals aimed at elucidating Geographical Reasoning, which led us to the identification of its possible constituent elements; (iii) the presentation of the historical context and structure of the normative documents analyzed, which allowed characterizations and generalizations of their content and meaning; and (iv) the identification, analysis and interpretation of the constituent elements of Geographical Reasoning in the normative documents, which led us to diagnose approximations and distances in relation to previously established references. In view of this, it was found that the BNCC/Geography contemplates, to a substantial extent, the development of Geographical Reasoning, which suggests that this regulation meets contemporary issues in the research field of teaching Geography. On the other hand, it was found that the Indicazioni Nazionali/ Geography does not fully contemplate the constituent elements of Geographical Reasoning according to the previously recommended references. It is noted that, in the comparison of the information and data discussed here, it was possible to perceive that both in Brazil and in Italy, there is still a long way to go with a view to the evolution of Geography teaching, whether in the field of regulations themselves, or in the field of its effective practice at school and in the classroom.